Trust and Patrimony - Smith, Lionel (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2008)
The French jurist Pierre Lepaulle argued that the common law trust could be best understood, in civilian terms, as a patrimony by appropriation. This argument has been influential in some civilian receptions of the trust. In fact, Lepaulle misunderstood the nature of the common law trust, which is founded on the obligations owed by the trustee in relation to the trust property. The rights of beneficiaries in the common law trust are neither purely personal rights against the trustee, nor are they real rights in the trust property, but rather they are rights over the rights which the trustee holds as trust property; they have a proprietary character since they persist against many third party transferees of the trust property. This analysis of the common law trust leads to the conclusion that it would be a fundamental change to turn the common law trust into a legal person. More generally, it is argued that any legal system that characterizes the trust as a legal person will find that it has ceased to understand the trust as a fundamental legal institution.